125 Years of Indian Forest Service Challenges, then and Now - Das, B. L. (Indian Forester, 1992)
The paper traces the changing face of the Indian Forester over 125 years of his existenee. The forester, initially starting as adventure and surveyor, graduate to the role of Police Officer and Magistrate by the beginning of the present century. His scientific acumen came into being in the beginning of the present century when his role as a silviculturists came to the fore, he was increasingly involved in afforestation and forest utilisation from 1925 onwards. The paper extensively analyses Sh. G.G. Takle's role in providing leadership to Indian forestry. The paper enlists the dawn of social forestry as a land mark in need based forest management. Recent advances in forest administration are also highlighted. Forest protection is seen as the most serious challenge being faced by the forester of the day.